Limon Creole Phrases: A Vehicle for Linguistic and Cultural Preservation - Pizarro Chacón, Ginneth (2015)
Phrases and idiomatic expressions used in everyday speech in Limon Creole by a group of elderly people have been collected in the province of Limon, Costa Rica, to preserve those phrases as part of their legacy to future generations. Considering the age factor, the information was gathered by applying a questionnaire to 50 native speakers of Limon Creole. Recommendations are provided, based on the results of the study.